Carbon Estimation in Three-Year-Old Ex-Field Shrub Vegetation in Ujoh Bilang Village Mahakam Ulu Regency, East Kalimantan Province - Zikri Azham; Steffani Huring; Hj. Maya Preva Biantari; Ismail Ismail (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Carbon Estimation in Three-Year-Old Ex-Field Shrub Vegetation in Ujoh Bilang Village, Mahakam Ulu Regency, East Kalimantan Province. The purpose of this study was to estimate the carbon content of shrub vegetation that had been abandoned for three years in Ujoh Bilang Village, Mahakam Ulu Regency. Vegetation sample data were collected according to the growth rate, namely in plots measuring 20 x 100 m, sub plots 10 x 50 m and research plots 1 x 1 m, the samples were plant vegetation, litter, necromass and dead wood. cVegetation samples were dried in an oven. The data were processed and calculated using the biomass formula and converted to carbon content per hectare. The results obtained from this study are the carbon content of dead wood nekormas of 12 tons/hectare, understorey vegetation of 0.609 tons/hectare, litter of 0.604 tons/hectare, and the total carbon content of shrub vegetation that has been abandoned for three years is 13,213 tons. /hectare.